Cropland suitability assessment using multi criteria evaluation techniques and geo-spatial technology: A review - SHALOO; BISHT, HIMANI; JAIN, RAJNI; SINGH, RISHI PAL (The Indian Journal of Agricultural Sciences, 2022)
Cropland suitability assessment is an essential technique for agricultural development and future planning. It is an evaluation to determine how suitable the land is for growing a specific crop in a particular region based on multiple parameters like soil, climate, topography, socio-economic condition, infrastructure, irrigation, existing land use/land cover and environmental aspects. The paper presents different multi-criteria evaluation (MCE) techniques such as Analytical Hierarchy Process (AHP), Fuzzy Analytical Hierarchy Process (FAHP), Analytic Network Process (ANP), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and ELimination Et Choice Translating REality (ELECTRE) approaches integrated with geospatial technology, namely remote sensing and Geographical Information System for cropland suitability assessment. Review findings indicate that the AHP technique was used by 53% of the researchers, followed by FAHP (16%); ANP (6%); TOPSIS (6%); ELECTRE (3%) and other techniques (16%) with or without geospatial technology. The integrated approach of MCE with geospatial was used by 69%, among which AHP technique of MCE was used by 72%; whereas, 22% used geospatial and 9% used MCE techniques alone. The results from the selected research articles also indicated that the most important input parameters were soil, topography and climate used by 97%, 88% and 74% of the researchers, respectively. The review can be helpful for researchers and decision-makers to select the most robust methods and standard parameters required for cropland suitability assessment to achieve higher agricultural production on a sustained basis.